2019
DOI: 10.1590/1984-6398201914813
|View full text |Cite
|
Sign up to set email alerts
|

Racism in English Language Teaching? Autobiographical Narratives of Black English Language Teachers in Brazil

Abstract: A hundred thirty years after the abolition of slavery and post-slave trade in Brazil, Black people remain the minority amongst teachers in English courses of private and public schools. This situation is tagged in their professional situation insofar as an aftermath of racism and coloniality are concerned, as I shall argue here. In this study, I seek to examine the ways race can be negatively or positively expanded in the performance of the identities of Black English language teachers, framing themselves as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…The dendrogram and the factorial representation of the classes obtained by the Iramuteq software (Figure 2) showed that the class of words most frequently found in the text segments was related to emotional aspects, challenges, doubts, fears, and beliefs, as is common in reports of this type [1,33]. The second class of most frequent terms highlights the teachers' concern to fulfil their role with quality and effectiveness, so teaching and learning processes and terms related to success and the understanding of content are also very frequent.…”
Section: Discussionmentioning
confidence: 98%
“…The dendrogram and the factorial representation of the classes obtained by the Iramuteq software (Figure 2) showed that the class of words most frequently found in the text segments was related to emotional aspects, challenges, doubts, fears, and beliefs, as is common in reports of this type [1,33]. The second class of most frequent terms highlights the teachers' concern to fulfil their role with quality and effectiveness, so teaching and learning processes and terms related to success and the understanding of content are also very frequent.…”
Section: Discussionmentioning
confidence: 98%
“…Portanto, representar o falante nativo como uma pessoa branca contribui para a construção de um círculo vicioso de manutenção de privilégios. Ser a única pessoa negra ou uma das poucas pessoas negras em um ambiente prejudica os processos de identifi cação com a língua inglesa e com a profi ssão (JONES, 2016;NASCIMENTO, 2019). Seria possível afi rmar que a falta de identifi cação com as imagens difundidas inibe a vontade de pessoas negras de aprender a língua inglesa e, consequentemente, de ingressar em cursos de licenciatura.…”
Section: O Professor De Língua Inglesa E O Falante Nativo Idealunclassified
“…A falta de atenção aos alunos negros e negras também elucida como a brancura faz parte do ensino de língua inglesa, pois parte da concepção que o processo de formação de professores pode ser color blind, isto é, não precisa considerar as questões raciais (SLEETER, 2017). Logo, não abordar tais questões e ignorar as necessidades do grupo minoritário contribui para a manutenção de um ensino pautado pela brancura dos falantes de língua inglesa (SLEETER, 2017;NASCIMENTO, 2019).…”
Section: O Professor De Língua Inglesa E O Falante Nativo Idealunclassified
See 2 more Smart Citations